ORGANIZATIONAL BUREAUCRATIC REFORM IN IMPROVING THE QUALITY OF PUBLIC SERVICES AT THE SECRETARIAT OF THE SURABAYA CITY RPRA - Agus Sunarto; Amirul Mustofa; Eny Haryati (Halu Oleo University, 2025)
This study aims to analyse organisational bureaucratic reform to improve the quality of public services in the Secretariat of the Surabaya City RPRA. This institution plays a strategic role in supporting legislative functions and bridging communication between the public and the people's representatives. However, bureaucratic complexity, rigid organisational structures, and limitations in responsiveness and technology utilisation are major challenges. Bureaucratic reform is carried out with a structural and cultural approach, such as organisational restructuring, digitising services, strengthening human resource competencies, and instilling a culture of excellent service. This study uses a qualitative and quantitative approach through a questionnaire instrument based on the Servqual theory (Parasuraman), which includes five dimensions of service: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results of the study showed a significant increase in all service dimensions, with the average community satisfaction above 84%. Bureaucratic reform has proven to be able to create public services that are faster, accountable, transparent, and oriented towards user satisfaction.